2016
DOI: 10.1016/j.nbd.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide alterations in hippocampal 5-hydroxymethylcytosine links plasticity genes to acute stress

Abstract: Environmental stress is among the most important contributors to increased susceptibility to develop psychiatric disorders, including anxiety and post-traumatic stress disorder. While even acute stress alters gene expression, the molecular mechanisms underlying these changes remain largely unknown. 5-hydroxymethylcytosine (5hmC) is a novel environmentally sensitive DNA modification that is highly enriched in post-mitotic neurons and is associated with active transcription of neuronal genes. Recently, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 68 publications
6
40
0
Order By: Relevance
“…Sodium bisulfite modification cannot distinguish between 5-methyl cytosine (5-MC) and 5-hydroxy methyl cytosine (5-HMC) levels. Like 5-MC, 5-HMC can vary in the brain in response to stress [47, 48] and has been identified in various psychiatric disorders [49, 50]. Brain tissue analyses have the potential to be confounded by postmortem factors such as the method and timing of tissue preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium bisulfite modification cannot distinguish between 5-methyl cytosine (5-MC) and 5-hydroxy methyl cytosine (5-HMC) levels. Like 5-MC, 5-HMC can vary in the brain in response to stress [47, 48] and has been identified in various psychiatric disorders [49, 50]. Brain tissue analyses have the potential to be confounded by postmortem factors such as the method and timing of tissue preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Related to disease, 5hmC functions independently from 5mC in neurological disorders ( e.g., Rett syndrome and Autism) (Mellen et al, 2012; Papale et al, 2015; Zhubi et al, 2014) and neurodegenerative diseases ( e.g., Huntington’s and Alzheimer’s) (Chouliaras et al, 2013; Condliffe et al, 2014; Wang et al, 2013). We recently reported a genome-wide disruption of 5hmC in the hippocampus of male mice exposed to acute stress followed by a one-hour recovery (Li et al, 2016). The differential 5hmC pattern significantly resided in known stress-related genes, which serves to validate a role for 5hmC in response to stress and also reveals potentially novel stress-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the hippocampus of stressed animals, the 3 ′ -UTR of the glucocorticoid receptor gene Nr3c1 was hyper-hydroxymethylated, a modification associated with increased transcription (Li et al 2015). These parallel studies also identified a pattern of hydroxymethylation throughout the genome in stressed animals, with many sites of differential hydroxymethylation located on known stress-related genes that were concomitantly changed at the mRNA level (Li et al 2016). These large-scale data sets suggest that even brief stressors induce epigenetic patterns that are capable of changing the global transcriptional profile of the brain by creating an environment that is permissible for the up-regulation of stress response genes.…”
Section: The Neuroepigenetics Of Stressmentioning
confidence: 78%